FEATURES OF FACIAL RECOGNITION - Malikova Ф.У; Zhanat Н.Ж; Saginayeva, A.K; Ryskeldy Р.С (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The facial recognition system is used to provide identification and authentication during functional testing. It can also be used to identify people in different situations. This article presents a comparative study of the algorithms used for facial isolation and recognition. Algorithms are general algorithms that match a recognizable face. The concept of each algorithm is explained and a corresponding description is given. In addition, the results of the algorithms are evaluated in a data set and are displayed as graphs for evaluating the effectiveness of each algorithm. Algorithms work with a common data set and display the percentage of functions obtained.